2001
DOI: 10.1021/ja0026915
|View full text |Cite
|
Sign up to set email alerts
|

[2+3] Cycloaddition of Ethylene to Transition Metal Oxo Compounds. Analysis of Density Functional Results by Marcus Theory

Abstract: Density functional results on the [2+3] cycloaddition of ethylene to various transition metal complexes MO(3)(q) and LMO(3)(q) (q = -1, 0, 1) with M = Mo, W, Mn, Tc, Re, and Os and various ligands L = Cp, CH(3), Cl, and O show that the corresponding activation barriers DeltaE(double dagger) depend in quadratic fashion on the reaction energies DeltaE(0) as predicted by Marcus theory. A thermoneutral reaction is characterized by the intrinsic reaction barrier DeltaE(0) of 25.1 kcal/mol. Both ethylene [2+3] cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…In order to evaluate thermodynamical and kinetic effects of activation processes, we used the Marcus theory [80][81][82][83][84][85] to separate their contributions to reaction barrier. The method was originally developed for describing charge transfer problems, and now it has been widely applied to various organic reactions [86][87][88][89][90][91][92][93]. In a reaction, the activation barrier (DE -) is composed of intrinsic barrier ðDE -0 Þ and thermodynamic contribution ðDE -therm Þ and can be described as…”
Section: Computational Detailsmentioning
confidence: 99%
“…In order to evaluate thermodynamical and kinetic effects of activation processes, we used the Marcus theory [80][81][82][83][84][85] to separate their contributions to reaction barrier. The method was originally developed for describing charge transfer problems, and now it has been widely applied to various organic reactions [86][87][88][89][90][91][92][93]. In a reaction, the activation barrier (DE -) is composed of intrinsic barrier ðDE -0 Þ and thermodynamic contribution ðDE -therm Þ and can be described as…”
Section: Computational Detailsmentioning
confidence: 99%
“…At first sight, this might seem to contradict well established quantum chemical calculations, which showed that the osmate ester formation is highly exergonic. The calculated energy changes for ethylene as an oxidizable alkene were −21.2 kcal mol −1 (=−88.7 kJ mol −1 ) and −18.1 kcal mol −1 (=−75.7 kJ mol −1 ) . Without the intention to question the accuracy of these results, the next paragraphs will show that the results of these quantum chemical calculations are irrelevant for the present study.…”
Section: Discussionmentioning
confidence: 79%
“…The calculated energy changes for ethylene as an oxidizable alkene were −21.2 kcal mol −1 (=−88.7 kJ mol −1 ) [46] and −18.1 kcal mol −1 (=−75.7 kJ mol −1 ). [47] Without the intention to question the accuracy of these results, the next paragraphs will show that the results of these quantum chemical calculations are irrelevant for the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Marcus theory was originally developed for electron‐transfer reactions . Subsequently, it has been successfully applied to a wide variety of organic reactions, such as cyclization …”
Section: Methodsmentioning
confidence: 99%